Johnmiedema.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

## Sagot :

4x² - 11x - 3 = 0

4x² -12x + x - 3 = 0

4x (x - 3) + 1(x - 3) = 0

(x - 3) (4x + 1) = 0

Using zero product property,

Either,

x - 3 = 0

x = 3

Or,

4x + 1 = 0

4x = -1

x = -1/4

(4x+1)(x-3)=0

We can solve for x by setting each parentheses equal to 0

x= -1/4

x= 3